Նոր բառերի մեքենական որոնման խնդիրները - Ֆրիդա Հակոբյան (ՀՀ ԳԱԱ հրատ.)
В последние десятилетия лингвисты уделяют особое внимание созданию словарей неологизмов. Текущие словари неологизмов не отражают общую картину неологизмов, потому что без какой-либо технической помощи невозможно получить все неологизмы, используемые в текстах.In the last decades linguists have paid a special attention to the creation of dictionaries of neologisms. It is conditioned by the lack of a dictionary reflecting the current state of the Armenian vocabulary.
Keywords: Philology; Linguistics; Science; Mathematics; Computer software